Physician beliefs about the impact of meaningful use of the EHR - Emani, S.; Ting, D.Y.; Healey, M.; Lipsitz, S.R.; Karson, A.S.; Einbinder, J. S.; Leinen, L.; Suric, V.; Bates, D.W. (Applied Clinical Informatics, 2014)
Background: As adoption and use of electronic health records (EHRs) grows in the United States, there is a growing need in the field of applied clinical informatics to evaluate physician perceptions and beliefs about the impact of EHRs. The meaningful use of EHR incentive program provides a suitable context to examine physician beliefs about the impact of EHRs.Objective: Contribute to the sparse literature on physician beliefs about the impact of EHRs in areas such as quality of care, effectiveness of care, and delivery of care.Methods: A cross-sectional online survey of physicians at two academic medical centers (AMCs) in the northeast who were preparing to qualify for the meaningful use of EHR incentive program.Results: Of the 1,797 physicians at both AMCs who were preparing to qualify for the incentive program, 967 completed the survey for an overall response rate of 54%. Only 23% and 27% of physicians agreed or strongly agreed that meaningful use of the EHR will help them improve the care they personally deliver and improve quality of care respectively. Physician specialty was significantly associated with beliefs; e.g., 35% of primary care physicians agreed or strongly agreed that meaningful use will improve quality of care compared to 26% of medical specialists and 21% of surgical specialists (p=0.009). Satisfaction with outpatient EHR was also significantly related to all belief items.Conclusions: Only about a quarter of physicians in our study responded positively that meaningful use of the EHR will improve quality of care and the care they personally provide. These findings are similar to and extend findings from qualitative studies about negative perceptions that physicians hold about the impact of EHRs. Factors outside of the regulatory context, such as physician beliefs, need to be considered in the implementation of the meaningful use of the EHR incentive program.Citation: Emani S, Ting DY, Healey M, Lipsitz SR, Karson AS, Einbinder JS, Leinen L, Suric V, Bates DW. Physician beliefs about the impact of meaningful use of the EHR: A cross-sectional study. Appl Clin Inf 2014; 5: 789–801http://dx.doi.org/10.4338/ACI-2014-05-RA-0050
Keywords: Electronic health records; physicians; beliefs; meaningful use; evaluation